Immunization Against Inhibin Promotes Fertility in Cattle: A Meta-Analysis and Quality Assessment - Ma, LingLi; Li, Zhuo; Ma, ZhongRen; Ma, JianBo; Zhao, Fei (Frontiers in Veterinary Science, 2021)
Superovulation and embryo transfer techniques are important methods in cattle breeding. Combined with traditional superovulation protocols, immunization against inhibin can further improve follicular development and embryo yield. The aim of this study is to determine the efficacy of immunization against inhibin in improving the fertility of cattle through meta-analysis, and to provide better clinical veterinary practice guidance. Three English database (PubMed, EMBASE, Web of Science) were searched for research articles of immunizations against inhibin influence on cattle fertility. Literature screening, data extraction, and meta-analysis were conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. In addition, the Systematic Review Center for Laboratory animal Experimentation (SYRCLE) risk of bias (RoB) tool was used to assess the risk bias of the included animal studies. Potentially relevant studies (317) were identified, and finally 14 eligible studies (all in English) were included. The results of meta-analysis revealed that immunization against inhibin has significant effects on improving the number of ovulation(mean difference (MD) =0.44, 95% confidence interval (CI) = [0.31, 0.56]), embryos and unfertilized ova (MD = 4.51, 95% CI = [2.28, 6.74])，follicles of the 3 size categories, the incidence of multiple ovulations(OR= 22.50, 95% CI = [8.13, 62.27]), and the conception rate (OR= 2.36, 95% CI = [1.26, 4.40]), Moreover, it improving the production of embryos (grades 1 embryos: MD=3.84, [3.54, 4.15]; grades 2 embryos: MD= -0.73, [-0.89, -0.57]; grades 3 embryos: MD= -0.50, [-0.75, -0.25]; degenerated embryos: MD= 1.16, [-0.51, 2.82]; transferable embryos: MD= 2.67, [2.03, 3.31]) and the number of corpora lutea (MD = 1.25, 95% CI = [0.79, 1.71]). In above indicators, the differences between the two groups were statistically significant (all P < 0.0001). Additionally, according to the quality evaluation results, the risk of bias in the included studies relatively high. The quality evaluation of the results of the included studies showed that the risk of bias mainly concentrated in the selective, performance, detection and reporting bias aspects.